The effect of blind box product uncertainty on consumers’ purchase intention: The mediating role of perceived value and the moderating role of purchase intention - Zhang, Yi; Zhang, Tianqi (Frontiers in Psychology, 2022)
As the young generation becomes the main consumption force and the traditional consumption culture changes, blind box has become a popular product among Chinese young generation with its uncertain characteristics. Existing studies mainly explore the impact of uncertainty in the context of promotion. Taking the emerging product blind box as the research object, this paper reviews the SOR theory and other relevant literature that forms the basis of our hypothesis that uncertainty increase blind box purchase intention and that perceived value, especially emotional value, has a mediating effect on the uncertainty on the purchase intention. We further hypothesize that the effect of the uncertainty on perceived value as well as the effect of the perceived value on purchase intention is moderated by customer consumption purpose. The conclusion is of guiding significance to enterprises how to make use of uncertainty in marketing.